PENGETAHUAN IBU TENTANG PEMBERIAN PARACETAMOL PASCA IMUNISASI DASAR DI UNIT BALAI KESEHATAN IBU DAN ANAK (BKIA) RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Samgryce Siagian, Hartika (JIFI (Jurnal Ilmiah Farmasi Imelda), 2023)
Immunizations must be given to children from birth so that their bodies are protected from dangerous diseases. Complete basic immunizations that have fever side effects are DPT and measles immunizations, while BCG, polio and hepatitis B immunizations cause pain around the injection and redness. Antipyretics are used to treat high fever and seizures due to fever after immunization. This study aims to determine the level of experince of mothers about giving paracetamol after basic immunization to children at the mother and child health clinic (MCH) RSU Imelda Pekerja Indonesia Medan. The sample used in this study was 30 people. This research is a quantitative descriptive study with a time series approach. The results of this study indicate that the characteristics of the mother's greatest level of work are housewives (66.7%) and the highest level of education of mothers is high school (53.3%). The mother's level of experince about giving paracetamol after immunization showed that the mother had a good level of experince (70%). In addition, the type of immunization that was given the most to children was BCG immunization (40%), where the age of the most immunized children was 2 months (20%). In addition, each child who was given paracetamol after BCG immunization was 4 children (13.3%). The average age of mothers who bring their children immunized is 24-26 years old (16.7%).